2021
DOI: 10.1128/mbio.00975-21
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Colonization of Microbes and Their Functions after Fecal Microbiota Transplantation for Inflammatory Bowel Disease

Abstract: Fecal microbiota transplantation (FMT)—transferring fecal microbes from a healthy donor to a sick patient—has shown promise for gut diseases such as inflammatory bowel disease. However, unlike pharmaceuticals, fecal transplants are complex mixtures of living organisms, which must then interact with the microbes and immune system of the recipient.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 67 publications
(95 reference statements)
2
37
0
Order By: Relevance
“…We find that, as has been shown in past studies 23 , the use of strain haplotypes inferred from SNP profiles 22 greatly improved the sensitivity of our transmission analysis. While this was expected given the large number of shared taxa at the species and 16S rRNA gene amplicon SNV levels, it is surprising that this improvement was possible without tuning hyper-parameters of the Strain Finder algorithm.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We find that, as has been shown in past studies 23 , the use of strain haplotypes inferred from SNP profiles 22 greatly improved the sensitivity of our transmission analysis. While this was expected given the large number of shared taxa at the species and 16S rRNA gene amplicon SNV levels, it is surprising that this improvement was possible without tuning hyper-parameters of the Strain Finder algorithm.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, features of the microbiome, in either patients or their donors, that predict FMT efficacy have not been convincingly identified 19 21 . An important challenge for understanding the role of engraftment is in distinguishing taxa originating in donors’ or recipients’ microbiomes 22 , 23 . While statistical approaches like SourceTracker, which models samples as blends of taxa from multiple sources, have been effectively applied to both 16S rRNA gene 24 and metagenomic surveys 25 , most tools for taxonomic analysis of microbial communities cannot differentiate between donor and patient populations of the same species, due to limited taxonomic resolution 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we will be able to develop precise therapeutic strategies for patients having similar individual disease spectrums to treat IBD. (Colman and Rubin, 2014;Costea et al, 2017;Nishida et al, 2017;Ishikawa et al, 2018;Goyal et al, 2018;Allegretti et al, 2019;Caruso et al, 2020;Ng et al, 2020;Chu et al, 2021;Saha et al, 2021) Anti-TNF Inhibiting the inflammation of TNF (Aden et al, 2019;Zhuang et al, 2020) Diet (EEN) Change the composition of the microbiota (Heerasing et al, 2017;Lewis and Abreu, 2017;Levine et al, 2018;Pigneur et al, 2019;Jongsma et al, 2020) Vedolizumab Inhibit the migration of lymphocytes from vascular endothelium to intestine (Stevens et al, 2017;Fleisher et al, 2018) Gut Target IL-12 and IL-23 (Feagan et al, 2016;Bradley, 2017) Tofacitinib, Filgotinib, and Upadacitinib Target Janus kinases (Hanauer et al, 2020;Feagan et al, 2021;Parigi et al, 2021) Tungstate inhibit the proliferation of Enterobacteriaceae (Zhu et al, 2018) FMT, fecal microbiota transplantation; Anti-TNF, anti-tumor necrosis factor; EEN. Exclusive enteral nutrition; HABN, Hyaluronic acid-coated bilirubin nanodrug.…”
Section: Future Directionmentioning
confidence: 99%
“…To date, several clinical trials have shown that intensive dose and multi-donor FMT could induce clinical and endoscopic remission ( Moayyedi et al., 2015 ). However, one study found that the transferred microbes in the recipient who underwent FMT 10 weeks later were far from the donor bacteria, which provide a critical issue that the colonization dynamics of gut microbiota should be tracked and manipulated in the recipient of FMT ( Chu et al., 2021 ). In addition, FMT is currently being investigated in registration and ethical clinical research, and it has not been approved for clinical application.…”
Section: Microbiota-targeted Treatment In Ibdmentioning
confidence: 99%
“…Several tools have been developed that take this approach, including Lineage (O’Brien et al, 2014), Strain Finder (Smillie et al, 2018), DESMAN (Quince et al, 2017), and ConStrains (Luo et al, 2015). These methods have been used to track the transmission of inferred strains from donors’ to recipients’ microbiomes after fecal microbiota transplantation (FMT) (Smillie et al, 2018; Chu et al, 2021; Watson et al, 2021; Smith et al, 2022). The application of strain deconvolution has been limited, however, by the computational demands of existing methods, where runtimes scale poorly with increasing numbers of samples, latent strains, and SNPs considered.…”
Section: Introductionmentioning
confidence: 99%